Congenital Adrenal Hyperplasia: Review from a Surgeon’s Perspective in the Beginning of the Twenty-First Century - PIAGGIO, LISANDRO A. (Frontiers in Pediatrics, 2014)
Congenital adrenal hyperplasia (CAH) most commonly due to 21-hydroxylase deficiency is the most common type of disorder of sex development. This review will focus on CAH addressing historical and current surgical techniques with their anatomical foundations, with special attention to long-term results and outcomes on sexual function, patient satisfaction, patient attitude toward surgery, and ongoing controversies in management of these patients.